Capturing Requirement Specification for Safety-critical System using SOFL and UML - Azma, Abdullah; Rohani, Abu Bakar; Roslina, Abd Hamid; Muhammad Zulfahmi Toh, Abdullah (2015)
This paper discusses two different types of capturing and presenting requirement specifications: UML and SOFL. The reason for choosing UML is because it employs an object-oriented approach, and SOFL is chosen as it is a combination of structured and object-oriented, which is an integration of Petri Net and VDM-SL. An On-Board Automation Systems is used to demonstrate how the two techniques work. Also, the differences between the two techniques is discussed, specifically with respect to the requirement in informal and semi-formal specifications.